Pengaruh Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Pegawai (Sensus Terhadap Pegawai Badan Kepegawaian dan Pengembangan Sumber Daya Manusia di Kota Tasikmalaya) - Aziza, Maisya Saadatul (CV. Kalimasada Group, 2023)
This research was conducted with the aim of determining the Effect of Work Discipline and Work Environment on Employee Performance at the Tasikmalaya City Human Resources Development and Personnel Agency. The method used inthis study is a quantitative method using data obtained directly through questionnaires distributed to 55 respondents who are employees of the Tasikmalaya City Human Resources Development and Personnel Agency. The data analysis technique used in this study is multiple linear regression analysis. Based on the results of the study, it can be seen that Work Discipline and Work Environment simultaneously have a significant effect on Employee Performance. Work Discipline partially has a significant effect on Employee Performance. The Work Environment partially has a significant effect on the Performance of Employees of the Tasikmalaya City Human Resources Development and Personnel Agency.